Analisis Logical Framework Approach terhadap Keberadaan Pasar Kalangan Desa dalam Pemenuhan Pangan Rumah Tangga di Desa Ulak Pianggu Kecamatan Pampangan Kabupaten Ogan Komering Ilir - Nurilla Elysa Putri; Armika Armika (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Putri NE, Armika A. 2021. The analysis of logical framework approach to the existence of village markets in fulfilling household food in Ulak Pianggu Village Pampangan District Ogan Komering Ilir Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 900-910. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Household food in rural areas is related to the availability of existing food access, one of the providers of food access in rural areas is the village market. The village market in South Sumatra is better known as the circle market. The purpose of this study was to identify efforts to increase the role of the village market in fulfilling household food in Ulak Pianggu Village. This study uses the Logical Framework Approach (LFA) method which consists of four analyzes, namely stakeholder analysis, problem analysis, objective analysis, and strategy analysis. The results of this study found that the market for Ulak Pianggu Village did not play a role in fulfilling household food, because the food available in the Ulak Pianggu Village market was incomplete. Based on the analysis of the Logical Framework Approach (LFA), a recommended solution was found, namely by increasing the availability of food types in the community market in order to increase the role of the village market in fulfilling household food in Ulak Pianggu Village.